Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Tang, Cindy Q.; Peng, Ming-Chun; He, Long-Yuan; Ohsawa, Masahiko; Wang, Chong-Yun; Xie, Tian-Hua; Li, Wen-Shun; Li, Jia-Ping; Zhang, Hong-Yu; Li, Yong; Yang, Xian-Ming; Li, Guo-Song (Journal of plant research, 2013)
The persistence of the Tertiary relict tree Tetracentron sinense Oliv. on the eastern slope of the Ailao Mountains, Yunnan, SW China, was here studied in terms of population structure (size, age) and regeneration patterns. T . sinense occurred in unstable habitats by stream banks, on steep slopes, on scree slopes, or on roadsides near streams in narrow valleys, all places subject to frequent natural disturbances, whereas none were found on stable gentle slopes free of major disturbances at similar altitudes. Further, no established saplings of T. sinense were found in forests having high bamboo ( Yushania crassicollis Yi) coverage in their understory. The size and age structure of T. sinense were multimodal. The reproduction of the tree was either by means of abundant minute wind-dispersed seeds or by resprouts in unstable habitats. These populations depended on disturbance or gap regeneration to survive. T. sinense , along with other tree life-forms including evergreen broad-leaved species and conifers, dominated in the forest canopy layer, even reaching the emergent layer in places. Results of the study provide insight into the ecological characteristics and survival mechanisms of this East Asian paleoendemic tree species. The study will provide a scientific basis for recommendations for the conservation of this species and for other Tertiary relict plants having similar regeneration dynamics.